Evaluation of Factors Affecting Farmers’ Calves Rearing Decision in West Java by Participatory System Analysis Approach - Achmad Firman; Sauland Sinaga; Rangga Setiawan; Dwi Suharyanto (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This research aimed to determine factors affecting farmers’ calves rearing decision and further determine which of the factors were categorized as the critical elements on the practice as well. A qualitative method was used in this research, where beef and dairy cattle farmer groups, dairy cooperative staffs, and regional department of livestock and animal health staffs were questioned as the source of information and data collection. The research area covered Tasikmalaya and Kuningan District for beef cattle rearing, while for the dairy cattle rearing covered Bandung and West Bandung District. The obtained data were then analyzed through Participatory System Analysis (PSA) approach. The results showed that factors which affect farmer’s dairy calves rearing decision were high-cost production, long rearing time, calves rearing status as a secondary income source, and reared calves’ quality. Furthermore, the results of this research also showed that the critical elements the decision were calves rearing status as secondary income and calves’ quality.